Attenborough's beauty: exceptional pattern preservation in a frog‐legged leaf beetle from the Eocene Green River Formation, Colorado (Coleoptera, Chrysomelidae, Sagrinae). (5th August 2021) - Krell, Frank‐Thorsten; Vitali, Francesco
Abstract: A new fossil leaf beetle species, Pulchritudo attenboroughi (Chrysomelidae, Sagrinae), is described from the Eocene Green River Formation in Colorado and is the second known fossil representative of this subfamily from North America. The fossil stands out by its remarkable preservation of elytral patterns. Such sharp and high‐contrast preservation of exoskeletal colouration is extremely rare in the fossil record of beetles and unique in its definition and fidelity. Sagrinae currently do not occur in North America, but two extant species are present in tropical and subtropical South America, one of which is similar in several aspects to the new fossil. Many extant Sagrinae live in a warm, humid climate similar to that suggested for the Early Eocene Climatic Optimum of the Green River Formation.